Variability in structure and carbon content of plankton communities in autumn in the waters south-west of the UK. (June 2022) - Capuzzo, Elisa; Wright, Serena; Bouch, Paul; Collingridge, Kate; Creach, Veronique; Pitois, Sophie; Stephens, David; van der Kooij, Jeroen
Highlights: The autumn bloom plays a major role for autumn-spawning fish and their larvae survival. Microphytoplankton dominated in autumn 2013, while nanophytoplankton in 2014. Silicate concentration was a key factor influencing plankton groups distribution. Highest plankton carbon was observed along the south coast of Cornwall. Lower plankton carbon was observed in the Bristol Channel, in both autumns. Observed zooplankton represented suitable prey for planktivorous small pelagic fish. Abstract: The size, type and abundance of planktonic organisms influence the efficiency with which carbon is transferred through the lower trophic levels, ultimately affecting dynamics at the higher trophic levels of the marine food web. In temperate shelf sea, such as the waters south-west of the UK, the plankton growing season span from early spring to autumn. While the plankton spring bloom has been extensively studied, the end of the growing season in September-October has received less attention, despite its potential importance for autumn-spawning fish and their larval stage survival. In this study we investigated the variability of the structure and carbon content of the planktonic communities in the waters south-west of the UK in October 2013 and 2014, discussing potential implications of these changes to small pelagic fish and higher trophic levels. Microphytoplankton (20–200 µm) dominated the plankton community in terms of carbon in 2013, while nanophytoplankton (<20 µm) in 2014. Ciliates, Copepoda, Decapoda and Cnidaria represented the highest proportion of carbon in the zooplankton component in both years, although ciliates and Copepoda biomass was higher in 2014. Environmental conditions were linked to these changes and were significant in describing the carbon content of the plankton groups. In particular, silicate concentration appeared to be a key variable, affecting diatom/plankton dynamics at the end of the growing season. Other important environmental variables associated with the structure of plankton groups were salinity, sea surface temperature, chlorophyll-a, difference between sea surface temperature and bottom temperature, phosphate and nitrogen concentrations. Although the composition and carbon distribution of the plankton community were different in the two years, cluster and Random Forest analyses showed similarities in the clusters of stations identified, defining an area of higher plankton carbon along the south coast of Cornwall, and an area of lower carbon in the Bristol Channel in both years. Presence of suitable prey for planktivorous small pelagic fish (e.g. Paracalanus and Pseudocalanus ), particularly in 2014, provided supporting evidence of the importance of this sea area as a foraging and nursery ground for sardines and other small pelagic fish, as well as for their predators.